The use of films as a teaching tool for the teaching-learning process in bioethics - Pereira Rates, Camila Maria; Maciel Silva, Larriny; Moura Pereira, Lívia; Dias Reis Pessalacia, Juliana (Investigación y Educación en Enfermería, 2014)
Objective. Identifying the contribution of using films in the process of teaching-learning in bioethics and verifying the facilities and difficulties in using this teaching resource. Methodology. A qualitative study analyzed from the Bardin referential. Semi-structured interviews were carried out, recorded, and transcribed in full. For definition of the sample was used the criteria of repetition. In total, participated in the study 21 students of Nursing and Biochemistry, members of a Center for Teaching and Research in Bioethics of a public federal university in the city of Divinópolis, Minas Gerais, Brazil. During the analysis of interviews, two thematic categories and two subcategories emerged. Results. In their responses, students indicated the importance of viewing the bioethical problem for the reflection and decision-making in professional practice. Many reported that from the experience in discussions of the films showed, were made changes in the ethical position. Conclusion: The use of films as a teaching resource contributes to the process of teaching-learning in bioethics for undergraduate students. The discussions of the films are stimulating and provide a space for reflection and dialogue on bioethical problems that students may encounter in their professional practice. How to cite this article: Rates CMP, Silva LM, Pereira LM, Pessalacia JDR. The use of films as a teaching tool for the teaching-learning process in bioethics. Invest Educ Enferm. 2014; 32(3):